2023
DOI: 10.1021/acs.analchem.3c03852
|View full text |Cite
|
Sign up to set email alerts
|

Stable SERS Detection of Lactobacillus fermentum Using Optical Tweezers in a Microfluidic Environment

Lindong Shang,
Peng Liang,
Lei Xu
et al.

Abstract: Rapid identification of fermented lactic acid bacteria has long been a challenge in the brewing industry. This study combined label-free surface-enhanced Raman scattering (SERS) and optical tweezer technology to construct a test platform within a microfluidic environment. Six kinds of lactic acid bacteria common in industry were tested to prove the stability of the SERS spectra. The results demonstrated that the utilization of optical tweezers to securely hold the bacteria significantly enhanced the stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…(C) SERS-based flow cytometry, reproduced from Sebba et al (2009 ). (D) SERS technology combined with optical tweezers in a microfluidic environment, reproduced from Shang et al (2023 ).…”
Section: Methods For Raman Signal Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…(C) SERS-based flow cytometry, reproduced from Sebba et al (2009 ). (D) SERS technology combined with optical tweezers in a microfluidic environment, reproduced from Shang et al (2023 ).…”
Section: Methods For Raman Signal Enhancementmentioning
confidence: 99%
“…The peaks of each lactic acid bacterium were significantly enhanced after SERS enhancement. This study revealed that the immobilization of bacteria using optical tweezers can significantly improve the stability of SERS spectra, expanding the practical application of SERS in bacterial detection ( Shang et al, 2023 ).…”
Section: Methods For Raman Signal Enhancementmentioning
confidence: 99%